English Language Use by Saudi Female Students in Higher Education: Insights for Educators and Policymakers - Almohaimeed, Nura; Alnasser, Suliman (International Journal of Language and Literary Studies, 2022)
Saudi higher education recognizes the importance of teaching and learning the English language, leading to the establishment of several academic English departments to fulfill national needs. Mastery of English in an EFL (English as a foreign language) context requires more frequent language use, both inside and outside the classroom domain. Current research suggests that investigations into Saudi students’ English language use inside the classroom have been addressed, but outside its boundaries and at the department level have yet to be addressed. This study aimed to address that gap to provide insights into female learners’ perspectives on the Saudi EFL learning environment. It adopted a mixed-methods approach for data collection. A seven-item survey with an open-ended section was filled out by Saudi female students (n = 381) studying in English departments nationwide. Additionally, semi-structured interviews with two questions were conducted with BA and MA English students (n = 10). The findings reveal the failure of Saudi English departments to provide students with the English practice opportunities they need and learners’ dissatisfaction with the current learning environment. The implications of the study include the urgent need for decision-makers to intervene and change the current status quo.